2018
DOI: 10.3389/fpsyt.2018.00545
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Addiction: From Evolution to Revolution

Abstract: The obesity epidemic has been widely publicized in the media worldwide. Investigators at all levels have been looking for factors that have contributed to the development of this epidemic. Two major theories have been proposed: (1) sedentary lifestyle and (2) variety and ease of inexpensive palatable foods. In the present review, we analyze how nutrients like sugar that are often used to make foods more appealing could also lead to habituation and even in some cases addiction thereby uniquely contributing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 287 publications
(308 reference statements)
2
60
0
10
Order By: Relevance
“…Our clinical experience suggests that failure to recognize/treat trauma/PTSD is a major contributor to poor outcomes. We have suggested that the proper interpretation of an FA diagnosis may improve treatment for those who would benefit from a different nutritional approach, such as excluding problematic foods like added refined sugars [ 234 ]. Evidence supports the validity of FA as a diagnostic construct, particularly as it relates to foods high in added sweeteners and refined ingredients [ 235 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our clinical experience suggests that failure to recognize/treat trauma/PTSD is a major contributor to poor outcomes. We have suggested that the proper interpretation of an FA diagnosis may improve treatment for those who would benefit from a different nutritional approach, such as excluding problematic foods like added refined sugars [ 234 ]. Evidence supports the validity of FA as a diagnostic construct, particularly as it relates to foods high in added sweeteners and refined ingredients [ 235 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug abuse and binge eating disorders share imbalances in brain systems that regulate motivation, reward saliency, decision-making, and self-control (Volkow et al, 2017;Wiss et al, 2018). Together with mesolimbic dopamine, the endogenous opioid system has been shown to play an important role in regulating food and drug reward (Volkow et al, 2013(Volkow et al, , 2017Berridge and Kringelbach, 2015).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…The strong affective and rewarding appeal of sweet taste may be a primary reason why sweet-tasting foods and drinks are eaten in excess, independent of the body's need for energy. Specifically, upon arrival of the sweetness-specific afferent signal from the periphery (e.g., mouth, gut) to the brain, dopaminergic pathways are activated causing an increased release of striatal dopamine [10] that is known to mediate the rewarding effects of food ingestion [11]. Operating in concert with dopaminergic neurons [12], a role of opioids in signaling the hedonic pleasure elicited from sweetness has been strongly supported in both the animal [13] and human literature e.g., in [14,15].…”
Section: Introductionmentioning
confidence: 99%